Preparing rhamnogalacturonan II domains from seven plant pectins using Penicillium oxalicum degradation and their structural comparison. (15th January 2018) - Wu, Di; Cui, Liangnan; Yang, Guang; Ning, Xing; Sun, Lin; Zhou, Yifa
Highlights: Penicillium oxalicum could degrade pectin to prepare RG-II domains. RG-II domains from 7 kinds of plants were prepared and analyzed. Side chain B of RG-II domain with DP 10 was discovered in prepared RG-II domains. Abstract: Rhamnogalacturonan II (RG-II) is a complex pectin with diverse pharmaceutical activities. To assess how RG-II functions, the development of methods for its preparation is required. In this paper, pectin from Codonopsis pilosula was used to evaluate the ability of fungi and bacteria to degrade the pectin. We discovered that the fungus Penicillium oxalicum could efficiently lead to the recovery of RG-II domains by degrading the other pectic domains. Further, six pectin fractions from different medical plants were used as the sole carbon source for the growth of Penicillium oxalicum . The major polymeric products remaining after fungus degradation was RG-II domains. Depending of plant source, side chains A differed with respect to their proportion of L-Gal and L-Fuc and to their degree of methyletherification. Side chains B were made of 8–10 sugar residues and up to 2 acetyl groups. Overall, our method provides an effective way to prepare RG-II pectin domains for investigating their structure-function relationships.